FINANCIAL FEASIBILITY OF LAYING CHICKEN ISA BROWN FARM (Case Study at UD. Aditya in Penebel District, Tabanan Regency, Bali) - Km., Widiastra; Sukanata, I W.; Putri, B. R. T. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
The study aims to determine financial feasibility and Break Even Point of laying chicken farm business was carry outfrom June 2018 to July 2018 at UD. Aditya located in Penebel District, Tabanan Regency, Bali Province. The data used are primary and secondary data was analyzed with analysis of investment criteria Pay Back Period, Break Even Point¸ and sensitivity analysis.This study indicated that laying chicken farm business resulted in NPV 1,943,774,054.91, IRR 19.7%, and Net B / C 1.34. Pay Back Period was achieved in time of 1.85 years while Break Even Point was achieved in time of 7.92 years, Break Even Point egg production can be achieved when the amount of production 3,102,537.02 eggs/year, or when the price of eggs Rp. 1.191.28/egg.Laying chicken farm business is sensitive to the increase of feed price which was equal to 14.47% and very sensitive to the decrease in egg price by 8.36% . It can be concluded that the laying chicken Isa Brown farm owned by UD. Aditya was financially feasibled .   Keywords: laying chicken, financial feasibility, investment criteria, sensitivity